Pendampingan Pengeolahan Tempe Sebagai Salah Satu Peluang Bisnis di Dukuh Krajan Desa Bedrug - Amalya Fauzianisa; Teguh Ansori (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This activity was carried out in Dukuh Krajan, Bedrug Village, Pulung District, Ponorogo Regency. Tempe is a nutritious food at an affordable prince. Even tempeh is included in the food that vegetarians like. Tempe processing can be made into a business field that is developed at home, to meet daily needs. From the stages of processing soybeans correctly and coherently, it will produce tempeh with the appropriate quality for marketing. Using the Asset Based Community Development (ABCD) method, this research can be carried out by way of direct interviews. The more enthusiasts for the tempe production, the greater the chance to be more successful in running this tempe production business.